Iron-chelating and anti-lipid peroxidation properties of 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) in long-term iron loading β-thalassemic mice - Kulprachakarn,K. (Elsevier BV, 2015)
© 2014 by the Asian Pacific Journal of Tropical Biomedicine. Objective: To evaluate the iron-chelating properties and free-radical scavenging activities of 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) treatment in chronic iron-loaded β-thalassemic (BKO) mice. Methods: The BKO mice were fed with a ferrocene-rich diet and were orally administered with CM1 [50 mg/(kg.day)] for 6 months. Blood levels of non-transferrin bound iron, labile plasma iron, ferritin (Ft) and malondialdehyde were determined. Results: The BKO mice were fed with an iron diet for 8 months which resulted in iron overload. Interestingly, the mice showed a decrease in the non-transferrin bound iron, labile plasma iron and malondialdehyde levels, but not the Ft levels after continuous CM1 treatment. Conclusions: CM1 could be an effective oral iron chelator that can reduce iron overload and lipid peroxidation in chronic iron overload β-thalassemic mice.